Spirituality, Justice, and Humanism in Human Existence: the Digital Discourse of War - Dobrodum , Olga (Skhid, 2026)
The article offers a comprehensive socio-philosophical analysis of the transformation of the discourse of spirituality, justice, and humanism in Ukraine under the influence of full-scale war and digitalization. The relevance of the study is determined by the need to understand how the fundamental values of human existence are being reinterpreted in the context of an existential crisis and "liquid modernity" (Z. Bauman), where traditional hierarchies give way to networked forms of communication, a defining feature of the information society. The research hypothesis is that war acts as a catalyst, shifting the discourse of spirituality, justice, and humanism from static hierarchical models to dynamic networked practices, where linguistic means, metaphorical models, and rhetorical strategies become key tools for constructing collective identity, legitimizing resistance, and forming an inclusive value space. The theoretical framework synthesizes Z. Bauman's concept of "liquid modernity," M. Castells' theory of the network society, J. Habermas' post-secular approach, and critical discourse analysis (N. Fairclough, T. van Dijk). The methodology combines secondary analysis of sociological data with discourse analysis of the digital content of Ukrainian denominations, as presented in authoritative media and scholarly research. The results reveal profound transformations: a shift from hierarchical to networked communication models, a reinterpretation of key values, the activation of metaphorical arsenals, and the emergence of inclusive linguistic strategies. Significant risks are identified: the digital divide, the tension between the universalism of humanism and the demonization of the enemy, and the threat of politicizing value discourse. The conclusions argue that the prospects for post-war development will depend on the ability of public institutions to develop inclusive dialogue strategies, preserving value pluralism in the conditions of the information society. The Ukrainian experience emerges as a representative model of the transformation of the discourse of fundamental values in the context of global instability.